Edukasi Tanggap Darurat Bencana Banjir Melalui Sosialisasi Kebencanaan - Amaliyah, Nur Azzatul; Priyanto, Anugerah Dany (LPPM Universitas Trunojoyo Madura, 2023)
Catastrophe such as floods can happen anytime and anywhere. PT. Mandala Cahaya Sentosa as a food industry must be wary to floods. If a flood happen, the company's operational activities will stop, so it can disturbing the production cycle. In addition, the puddle on the product will cause damage to the product, until the company have a loss. To solve the problem, socialization are needed to give education to employees of PT. Mandala Cahaya Sentosa in disaster management to minimize risks. The socialization of the flood emergency response held on May 23, 2023, attended by the Head of Production and Head of General Affair. The result of this socialization is increasing in preparedness and knowledge of employees PT. Mandala Cahaya Sentosa about flood emergency response, so that employees can do disaster management when a flood happen.